Proposição de uma ferramenta para identificação de indícios de disfunção em sistemas de indicadores de desempenho - Welter, Anelise Faleiro (Universidade do Vale do Rio dos Sinos, 2012)
Performance indicators play a key role in managing organizations in an environment increasingly competitive and globalized. When there is no performance evaluation, when the results of an organization are not measured, they can not be managed (GOLDRATT, 2002). However, the use of indicators, or even the use of indicator systems as the Balanced Scorecard (BSC), can also be detrimental to the organization and produce results contrary to those desired, thus characterizing the dysfunction of indicators. This dysfunction occurs when there is predominance and emphasis on financial indicators (temporal dysfunction), when there is local optimization over the global optimization (dysfunction by local optimization) and when indicators generate unwanted actions (behavioral dysfunction). In this context, this thesis, in addition to categorize, through a systematic review, the types of dysfunction as mentioned above, propose a tool for identifying evidences of this problem in systems of indicators from different organizations. The tool comprises seven stages of analysis that cover all three types of dysfunction and ends with step summary of the analysis’ results. To evaluate the tool, it is applied in a company that uses the BSC characterized the research as a Design Research.
Keywords: Indicator dysfunction; Performance indicators; Performance indicators systems; Performance evaluation; Disfunção de indicadores; Indicadores de desempenho; Sistemas de indicadores de desempenho; Avaliação de desempenho; ACCNPQ::Engenharias::Engenharia de Produção